2019
DOI: 10.1016/j.cmet.2019.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Lactate Buildup at the Site of Chronic Inflammation Promotes Disease by Inducing CD4+ T Cell Metabolic Rewiring

Abstract: Graphical Abstract Highlights d Lactate induces the expression of SLC5A12 on human CD4 + T cells in the inflamed tissue d Lactate promotes CD4 + T cell IL17 production via PKM2/ STAT3 signaling and FA synthesis d Lactate inhibits CD4 + T cell motility via increased FA synthesis and reduced glycolysis d SLC5A12 blockade ameliorates the disease severity in a murine model of arthritis

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
264
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 339 publications
(293 citation statements)
references
References 100 publications
(123 reference statements)
1
264
4
Order By: Relevance
“…Accumulation of lactate in the tissue microenvironment is also a feature of sepsis ( 10 ). It has been indicated that the physiological lactate concentration in blood or healthy tissues is approximately 1.5 – 3 mM ( 39 ), while the blood lactate levels in septic patients can reach over 20 mM ( 40 ). Remarkably, lactate levels can rise to 40 mM at the inflamed tissues ( 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…Accumulation of lactate in the tissue microenvironment is also a feature of sepsis ( 10 ). It has been indicated that the physiological lactate concentration in blood or healthy tissues is approximately 1.5 – 3 mM ( 39 ), while the blood lactate levels in septic patients can reach over 20 mM ( 40 ). Remarkably, lactate levels can rise to 40 mM at the inflamed tissues ( 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…Both peripheral and tissue resident RA CD4 + T cells have a unique metabolic signature (Weyand et al, 2017;Pucino et al, 2019). Indeed, RA CD4 + T cells exhibit an impairment in engaging glycolysis.…”
Section: Glucose Metabolismmentioning
confidence: 99%
“…High concentrations of lactic acid are found in both blood and synovial fluid from inflamed joints in RA patients. Several studies have shown that lactate promotes the aggressive phenotype of FLS [174], the pro-inflammatory properties of macrophages [152][153][154], stimulates IL-17 secretion by CD4+ T cells and, at the same time, decrease CD4+T migration, which is related to the maintenance of a chronic inflammatory infiltrate [155,175]. Moreover, recently, a new lactate induced histone modification was described, lactylation, which correlates with the levels of lactate and is different from acetylation [176].…”
Section: Pro-inflammatory Metabolitesmentioning
confidence: 99%